2000
DOI: 10.1034/j.1600-0706.2000.880302.x
|View full text |Cite
|
Sign up to set email alerts
|

Rodents, plants, and precipitation: spatial and temporal dynamics of consumers and resources

Abstract: Resource/consumer dynamics are potentially mediated by both limiting resources and biotic interactions. We examined temporal correlations between precipitation, plant cover, and rodent density, with varying time lags using long‐term data from two sites in the Chihuahuan desert of North America: the Sevilleta Long‐term Ecological Research site (LTER), New Mexico, USA and a site near Portal, Arizona, USA. We also calculated the spatial correlations in precipitation, plant cover, and rodent dynamics among six sit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

19
205
0
5

Year Published

2002
2002
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 216 publications
(229 citation statements)
references
References 75 publications
19
205
0
5
Order By: Relevance
“…A possible underlying mechanism for this finding is that temperature may affect the population density and hantavirus infection rate of rodents. 9,14,34 Some studies reported that environmental variables, including temperature, may affect population dynamics of the deer mouse. 14 Lower temperature in the winter may reduce the growth of rodents and the reproduction of hantavirus, and higher temperature may enable reservoirs to survive more easily in winters.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A possible underlying mechanism for this finding is that temperature may affect the population density and hantavirus infection rate of rodents. 9,14,34 Some studies reported that environmental variables, including temperature, may affect population dynamics of the deer mouse. 14 Lower temperature in the winter may reduce the growth of rodents and the reproduction of hantavirus, and higher temperature may enable reservoirs to survive more easily in winters.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8] However, the role of climate factors in the transmission of HFRS differs in different regions. 4,[6][7][8][9][10][11][12] For example, increased grass seed production followed by heavy precipitation, as a result of the El Niñ o Southern Oscillation (ENSO), was found to be associated with higher Peromyscus maniculatus rodent density in southwestern United States and provides reservoirs for Sin Nombre virus. 13,[15][16][17] However, this result was not duplicated in other areas in the United States.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Many factors can affect rodent population dynamics, including food availability, disease, and climatic variables, such as precipitation and temperature. [4][5][6][7][8][9][10][11][12] Seasonal fluctuations in the abundance of certain flea species also have been reported to be correlated with precipitation and temperature changes. [13][14][15][16][17] Additionally, the ability of fleas to transmit Y. pestis has been demonstrated to be temperature-dependent, with high temperatures (Ն 81.5ЊF, Ն 27.5ЊC) resulting in reduced rates of transmission.…”
Section: Introductionmentioning
confidence: 99%
“…The evolution of terrestrial life has been driven by the challenge of maintaining water balance with scarce freshwater resources, but effects of animal water limitation on terrestrial food webs have received little attention, in contrast to plant-mediated bottom-up effects [1,[2][3][4][5]. This is a significant gap in our understanding of ecological dynamics, because over 40% of the earth's land surface is classified as drylands [6] and precipitation limits diversity of plants and animals at all but the highest latitudes globally, even outside of drylands [7].…”
Section: Introductionmentioning
confidence: 99%